A crise democrática brasileira do século XXI sob a ótica de uma justiça de transição - Lopes, Natália Nunes (2022)
The research's main objective is to understand the institute of truth and memory from the events of the Military Dictatorship between the periods of 1964-1985 in the Brazilian State. In the same way, the research aims to emphasize the forms of resistance to times of human rights protection hiatus through transitional justice as an institute that provides social humanization. The work researches on how this juridical-sociological phenomenon and the consequent nonclarification of human rights violations that occurred in the period are related to the erosion of Brazilian democratic institutions and, above all, how the non-application of transitional justice contributed to the current panorama of democratic discredit and authoritarian rise to power. Furthermore, a critical analysis of the measures taken by the government when overcoming the military dictatorship was carried out since they proved to be insufficient to purge the tyrannical characteristics of the state structure. For that, the movement of “slow and gradual” political opening proposed by the dictatorial government was observed, culminating in the panorama of the promulgation of the Amnesty Bill. It is important to emphasize the results of the absence of transitional justice: failure of democratic institutions, constitutionalism in crisis, the rise of the counter-narrative to power, and the lack of education for human rights of the Brazilian people. In terms of methodology, the hypothetical-deductive method was chosen, which implies characteristics of deductive reasoning, as well as from inductive reasoning to research and identify the parts of the phenomenon and collect them in order to have a general perception or conclusion. It was also noticed the role of the dialectical method in a work of this nature, since the dialectical method presupposes a study of reality in its movement, analyzing the parts in constant association with the totality and enabling a holistic view of the phenomenon. In addition, the approach method is the historical materialism, given the political and social characteristics of the research. The research carried out is qualitative, and the bibliographic and documental analysis was used. To this end, the research structure is composed of three sections. In them, the conduct of state agents responsible for the violations of government opponents rights was discussed, and in which way the dictatorship was institutionalized through normative changes; the study of the transitional justice theory, choosing the elements of truth and memory as relevant institutes for the construction of democracy in addition to education for human rights in the society structured by the cultural industry; and the endurances and anachronisms in a society with remnants of authoritarianism, whose values are centered on anti-democratic ideals through denialist narratives that culminated in the current Bolsonaro government, whose main characteristic is the promotion of violence. Finally, the research used studies of deliberative democracy as a way of overcoming the current constitutional crisis.